Are Asian cultures really less ageist than Western ones? It depends on the questions asked. (4th July 2016) - Vauclair, Christin‐Melanie; Hanke, Katja; Huang, Li‐Li; Abrams, Dominic
Abstract : Ageism is an increasing concern in ageing populations such as Asia and Europe. A prevalent assumption in psychology is that Eastern cultures may be less prone to ageism because of norms and values that honour and respect elders. Yet, evidence for this culture hypothesis is inconclusive. The current study examines this issue by comparing attitudes towards older people in an Eastern and Western samples of 184 young people from the UK and 249 from Taiwan. Attitudes to old age were measured both as meta‐perceptions (the perceived normative context) and personal attitudes in regard to the cognitive, affective and behavioural components of ageism. Consistent with the culture hypothesis, meta‐perceptions about competence and admiration were more positive in Taiwan than in the UK, yet other meta‐perceptions were more negative pointing to the existence of old age subtypes. Personal attitudes about older people in regard to the affective and behavioural, but not the cognitive component, were more negative in Taiwan than in the UK. Thus, cultural differences in ageism are more nuanced than suggested by previous research. The importance of distinguishing between the normative context and personal attitudes as well as the different components of ageism is highlighted by the present findings.